1986
DOI: 10.1007/bf01300255
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone dissolution treatment with a combination of chenodeoxycholic and ursodeoxycholic acids

Abstract: Sixteen patients with radiolucent gallstones were treated with a combination of chenodeoxycholic and ursodeoxycholic acids for an average of 19 months. Liver tests remained normal in all patients. In nine of 15 patients (60%), in whom the gallbladder visualized during an oral cholecystogram, gallstones dissolved after one year, in eight of them, partially, and in the remaining one, completely. After two years, partial dissolution became complete in three patients, and partial dissolution occurred in 1 addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Gallstone disease is common and affects between 10 and 20% of the worlds population. Gallstones are classified by their composition into two main groups : cholesterol stones and pigment stones.…”
Section: Gallstone F ' O R M a T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstone disease is common and affects between 10 and 20% of the worlds population. Gallstones are classified by their composition into two main groups : cholesterol stones and pigment stones.…”
Section: Gallstone F ' O R M a T I O Nmentioning
confidence: 99%
“…Ursodeoxycholic acid (UDCA) is as effective as CDCA, is free from unwanted effects and a lower dose is required (8)(9)(10)(11)(12)(13) mg kg-' day-'). However, UDCA is more expensive and is reported to cause calcification of some radiolucent stones.'…”
Section: Dissolution Of Gallbladder Stonesmentioning
confidence: 99%
“…In the Western world, three‐fourths of gallbladder patients have cholesterol (Ch) stones, which contain 80% to 98% Ch by weight 1. For Ch gallstone patients, conjugated ursodeoxycholate (UDC), the 7β‐epimer of chenodeoxycholate (CDC), has been proven to be equal or superior to conjugated CDC in inducing Ch gallstone dissolution when administered orally 2–7. Nevertheless, previous in vitro studies showed that UDC and its conjugates (glycine and taurine) were poor Ch solubilizers relative to CDC and its conjugates 8–10.…”
Section: Introductionmentioning
confidence: 99%